2017
DOI: 10.9790/1959-0601025162
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nursing Care Standards for Preventing Deep Vein Thrombosis among Patients Undergoing Hip Surgery on Nurses' Performance and Patients' Outcome

Abstract: Abstract:Aim of this study wasto evaluate the effect of Nursing care standards (NCSs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…As regards to occurrence of DVT the findings of the present study revealed that there were statistically highly significant reductions of D.V.T occurrence for study group than control group at one week and two weeks postoperative. This result was in agreement with El-Sayed et al, (2016) who studied "effect of nursing care standards for preventing deep vein thrombosis among patients undergoing hip surgery " in orthopaedic unit and outpatient clinics at Benha university Hospital and found that there were decrease in all items related to clinical manifestations of DVT in study group than control group during and after one month from discharge and incidence of DVT among patients in study group was lesser than patients in control group. This may be related to instruction of researchers to study group patients about importance of early mobilization and postoperative exercises.…”
Section: Occurrence Of Postoperative Complications Among Studied Groupssupporting
confidence: 90%
“…As regards to occurrence of DVT the findings of the present study revealed that there were statistically highly significant reductions of D.V.T occurrence for study group than control group at one week and two weeks postoperative. This result was in agreement with El-Sayed et al, (2016) who studied "effect of nursing care standards for preventing deep vein thrombosis among patients undergoing hip surgery " in orthopaedic unit and outpatient clinics at Benha university Hospital and found that there were decrease in all items related to clinical manifestations of DVT in study group than control group during and after one month from discharge and incidence of DVT among patients in study group was lesser than patients in control group. This may be related to instruction of researchers to study group patients about importance of early mobilization and postoperative exercises.…”
Section: Occurrence Of Postoperative Complications Among Studied Groupssupporting
confidence: 90%
“…These findings highlight the relationship between knowledge and practice, showing that without accurate, sufficient knowledge, nursing practices will become more risky and ineffective. Similarly, The study Effect of Educational Guidelines on Nurses' Performance Regarding the Management of Patients Undergoing Bone Marrow Transplantation by Abed El-Hay et al (2018), found a statistically significant positive correlation between nurses' knowledge and practice and their socio-demographic characteristics, supported these findings.…”
Section: Discussionmentioning
confidence: 72%
“…Beside [25] demonstrated that, there was decrease in all items related to the clinical signs and symptoms of DVT in the study group than in the control group during and after one month from discharge and with statistically significant differences observed as (P≤ 0.001 & P<0.05) when studying effect of nursing care standards for preventing deep vein thrombosis.…”
Section: Discussionmentioning
confidence: 77%
“…An awareness of all aspects of DVT is vital in providingthe optimalnursing care for the patients who were undergoing surgery /delivery / or CS in order to improve the patients' outcomes, reduce the incidence and potentially lifethreatening complications of DVT [3] & [25].So, this study concerned on with the evaluation of the effect of calf muscle pump exercise and preventive measures on the prevention of deep vein thrombosis (DVT) and its manifestations among post-partum cesarean section.…”
Section: Significance Of the Studymentioning
confidence: 99%